Urinary tract infections in women in Catalonia, Spain: a population-based observational cohort study in primary care - Fernández-García, Silvia; Moragas, Ana; Giner-Soriano, Maria; Morros, Rosa; Ouchi, Dan; García-Sangenís, Ana; Llor, Carl (Frontiers in Pharmacology, 2025)
IntroductionUrinary tract infections (UTIs) are a frequent consultation in primary care and are usually treated with empirical antibiotics. Women suffer more from UTIs than men, and are therefore more likely to be treated with antibiotics. The aim of this study was to describe the epidemiology of UTIs in women in Catalonia, Spain.MethodsWe conducted a population-based observational cohort study that included women patients diagnosed with UTI and recurrent UTI within the SIDIAP and CMBD database during the period from 2012 to 2021. UTI diagnoses were grouped into two main groups, cystitis and pyelonephritis, and patients recorded as having 2 or more episodes of UTI within the year following the first recorded UTI were considered to have recurrent UTI.ResultsThe study identified 962,998 women with at least one UTI episode. Cystitis was the most frequently reported infection and was primarily treated with fosfomycin, aligning with local clinical guidelines. Pyelonephritis was typically managed with penicillins. Recurrent UTIs accounted for 3.7% of the sample.DiscussionThis large-scale cohort study provides a comprehensive overview of the epidemiology, management, and treatment of urinary tract infections in women in Catalonia. The findings highlight the widespread use of guideline-recommended antibiotics in the routine clinical management of cystitis, but not of pyelonephritis, and underscore the burden of recurrent infections in a small yet clinically significant subgroup of patients.